German Special Operations Forces: The case for revision - Timo Noetzel; Benjamin Schreer (Stiftung Wissenschaft und Politik (SWP), 2006)
Triggered by recent events in Afghanistan, Germany is debating the future role of its special operations forces (SOF). Particular criticism has focused on the lack of transpar-ency regarding the deployment of the Special Operations Forces (Kommando Spezialkräfte, or KSK) and on insufficient mechanisms for political oversight over these forces. The German government wants the KSK to continue to participate in Operation Enduring Freedom (OEF). However, in order to prevent further domestic political backlash against the use of these forces, there needs to be a political debate about the future role of SOF in German defense and security policy as well as a revision of current practice. (SWP-Comments / SWP)
Keywords: 320